Study of a prescribing pattern of empirical antibiotics in patients with sepsis in a tertiary care hospital of Eastern India - Lalatendu Mohanty; Debananda Sahoo; S. S. Panda; S Patro (International Journal of Medical Research and Review, 2016)
Background: Blood stream infections cause significant morbidity and mortality worldwide. Rational use of antimicrobials is required for proper management. Appropriate selection of empirical antibiotic therapy for diagnosed sepsis is difficult.Objective: The main objective of this study is to evaluate the prescribing pattern of antibiotics in patients with sepsis in a tertiary care hospital of Eastern India.Methods: The study was carried over a period of one year at the Department Of Medicine, Kalinga Institute of Medical Sciences (KIMS), Bhubaneswar. We studied 100 patients with sepsis regarding empirical antibiotics prescribed on initial evaluation.Results: As per the prescription analysis, the antibiotics used as empirical treatment based on class were penicillin derivatives (72%), macrolide (40%), nitroimidazole (40%), Cephalosporin(28%), fluoroquinolones (18%), aminoglycoside (13%), Carbapenems (3%) and oxazolidinone (4%). 56% patients received a combination of two antibiotics. We had seen improvement in 86% of the patients and discharged them. The rest were either shifted to the specialty care or left the hospital against medical advice.Conclusion: This study found that beta-lactam antibiotics like piperacillin, amoxyclav and cephalosporins are mostly used in the empirical treatment of sepsis. Early initiation of antibiotics is associated with improved outcomes in severe sepsis and septic shock. The addition of two or more antibiotics increases the coverage especially of Gram-negative bacteria.